Editorial: missed opportunities to detect colorectal cancer in inflammatory bowel disease—getting to the root. Issue 2 (25th December 2020) - Mahmoud, Remi; Itzkowitz, Steven H.
Abstract : LINKED CONTENT This article is linked to Gordon et al and Chee et al papers. To view these articles, visit https://doi.org/10.1111/apt.16155 and https://doi.org/10.1111/apt.16215